Revisiting the idea of vocation theological explorations - Haughey, John C. (Washington, D.C. : Catholic University of America Press, 2004)
Publisher's description: Until recently theologians have been in a deep slumber about the subject of vocations. This volume represents one of the first awakenings in the theological community to this subject. The ten contributors, all theologians at Loyola University Chicago, present original essays that explore vocations, or callings. There are several things that make this volume unique. As reflected in the diverse approach to the subject, theology is a multi-disciplinary, even inter-disciplinary field. Some of the authors delve into scriptural materials to enlighten readers on the notion of call. Others discuss the mystery of vocation in terms of spirituality, history, doctrine, psychology, or theology. Adding to the volume's uniqueness are essays written from a Jewish and from an Islamic perspective. The breadth and depth of these essays suggest how many splendored this topic is for those who teach students or minister to parishioners, counsel clients or guide directees. The reflections presented here will be useful to them and will restore interest in this long-neglected subject. Although the approaches represented by the essays are many, the calling of each person is to the One God whose holiness is intended for all peoples.
The three conversions embedded in personal calling / John C. Haughey -- The call of creation / Camilla Burns -- Vocation and call as individual and communal imperatives: some reflections on Judaism / Edward Breuer -- 'My food is to do the will of the one who sent me' (John 4:34): Jesus as model of vocation in the Gospel of John / Urban C. von Wahlde -- Islamic conceptions of vocation / Marcia Hermansen -- Vocation and the Spiritual exercises of St. Ignatius of Loyola / Paul F. Harman -- Trying to follow a call: vocation and discernment in Bunyan's Pilgrim's progress / Mark A. McIntosh -- Protestantism and the vocation of higher education / D.H. Williams -- Psychological dimensions of the discernment of vocation / John P. Neafsey -- Listening for a life's work: contemporary callings to ministry / Mary Elsbernd.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Vocation, Ecclesiastical; Vocation -- Catholic Church; Vocation sacerdotale; Vocation -- Église catholique; Berufung; RELIGION / Christian Life / General; Electronic books